Pengaruh Pengunaan Model Jigsaw Terhadap Kemampuan Mengidentifikasi Teks Ceramah Siswa Kelas XI SMK Negeri 3 Padang - Amelia Fitria Sari; Yulia Sri Hartati; Asri Wahyuni Sari (STKIP PGRI Sumatera Barat, 2021)
This research is motivated by the problem that some students do not understand the material about identifying lecture texts. The purpose of this study was to describe the ability to identify lecture texts for class XI students at SMK N 3 Padang without and using the Jigsaw learning model, and to describe the effect of the Jigsaw learning model on the ability to identify lecture texts for class XI students at SMK N 3 Padang. This type of research is quantitative research. The design of this study was a posttest only control design. The population in this study were class XI students of SMK N 3 Padang who were registered in 2019/2020. The research sample consisted of 30 control classes and 30 sample classes. The data of this study is the score of the test results of the ability to identify lecture texts without and using the Jigsaw learning model. Based on the results of the study, it was concluded as follows: First, the level of Ability to Identify Lecture Texts without using the Jigsaw model, class XI students of SMK N 3 Padang obtained an average score of 71.30 with a classification of 66-75%, which is more than adequate (LdC). Second, the level of ability to identify lecture texts after using the Jigsaw model, class XI students of SMK N 3 Padang obtained an average score of 79.68 with a classification of 76-85%, which is good (B). Third, from the results of data analysis that has been carried out that the use of the Jigsaw model has a significant effect on increasing the ability to identify lecture texts, it can be seen that the alternative hypothesis (H1) is accepted at a significant level of 95% and dk = n-2 because tcount > ttable ( 5.17 > 1.67).